Ingestão de sódio e desfechos renais em pacientes com doença renal crônica: revisão sistemática e metanálise - Cury, Cecília Malheiro [UNESP] (2024)
Background: Restriction of sodium intake is recommended for patients with chronic kidney disease. High sodium intake reduces the antiproteinuric effects of renin angiotensin aldosterone system inhibitors and increase blood pressure. However, if high sodium intake is associated with the progression of chronic kidney disease remains uncertain. We conducted a systematic review and meta-analysis to compare the effect of different range of sodium intake on chronic kidney disease progression. Objective: The objective of this study was to estimate the association between different ranges of sodium intake: (≥100-≤150 mEq/day (mEq/d); >150-≤200 mEq/day; >200 mEq/day), compared with the reference (< 100 mEq/day), and progression of CKD in adults with CKD undergoing non-dialysis treatment. Information sources: MEDLINE, EMBASE, LILACS, SCOPUS, Web of Science, Cinhal and Cochrane Library databases. Eligibility criteria: We included cohort studies with enrolled adults in non-dialysis chronic kidney disease with measured sodium intake using the 24-hour urinary sodium excretion method. We compared the reference (< 100 mEq/day) with the cut off points (≥100-≤150 mEq/day; >150-≤200 mEq/day; >200 mEq/day). The renal outcomes evaluated were: more than 50% decline in estimated glomerular filtration rate, doubling of serum creatinine or end-stage renal disease. Data extraction and risk of bias: Two independent researches extracted data and evaluated their quality. We used the Collaboration Joanna Briggs Institute checklist to evaluate the quality of cohort studies. Hazard ratios (HR) with 95% CIs was used for dichotomous data. The Higgins Inconsistency Test (I²) was used to assess the risk of bias between the studies and significance was defined when the I² result was greater than 50%. Results: We found 240 potential research records. After removing duplicates, reviewing titles and abstracts, 19 studies were selected for complete reading. However, only six studies filled all eligibility criteria. When comparing sodium intake ranges with reference (<100 mEq/day), the effect of studies unadjusted for proteinuria were: (≥100- ≤150 mEq/day (HR: 1.00; 95%CI: 1.00 to 1.00); ;>150-≤200 mEq/day (HR: 1.03; 95%CI: 0.87 to 1.21); >200 mEq/day (HR: 1.47; 95% IC: 0.84; 2.60). For studies adjusted for proteinuria: (≥100-≤150 mEq/day (HR: 1.00; 95%CI: 0.99 to 1.00); ;>150- ≤200 mEq/day (HR: 0.91; 95%CI: 0.78 to 1.06); >200 mEq/day (HR: 0.90; 95% IC: 0.75; 1.08). Conclusion: Different ranges of sodium intake were not associated with the risk of CKD progression as for studies unadjusted for proteinuria as studies adjusted for proteinuria. However, the recommend for the sodium intake restriction must be keep. Further, more studies are needed to clarify the association between sodium intake and progression of chronic kidney disease. PROSPERO: registration number CRD42020153275.